ENHANCING TAX ADMINISTRATION: STRATEGIES, CHALLENGES AND INNOVATIONS (Journal of Science-Innovative Research in Uzbekistan, 2024)
Tax administration plays a crucial role in ensuring effective revenue collection for governments. Improving tax administration involves implementing strategies and policies to enhance compliance, efficiency, and effectiveness in tax collection processes. This article explores various approaches to improve tax administration, including technology adoption, capacity building, taxpayer education, and policy reforms. It discusses the benefits of improving tax administration for economic development and suggests recommendations for policymakers and tax authorities to enhance tax collection efforts